Το πολιτικό σύστημα της Γερμανίας - Ο μετριασμένος κοινοβουλευτισμός (Μέρος 1ο) - ΙΩΑΝΝΗΣ ΠΑΠΑΓΕΩΡΓΙΟΥ (Αριστοτέλειο Πανεπιστήμιο Θεσσαλονίκης, 2022)
: My me my seat Louis more visa said the longer the horses E plus B movies Homa leave Yes I can Yes I feel you but we might be flying fun day push your goals be mammals in his mind you've got blushing I'm you know maybe my was the lone was no Hey you're a baby boy OK go ahead say you all know this copy of increased fear of I was mango good goal people than usual you lose control Yeah I like me he here do you team next season listen swimming with writing my Yeah I mean you know Yes Yes day I'm a read but what is your one of the most of my rule we want Maria all the commissioners told all these we needed every you'll see gosh my mom online business there's KOCO You must sign goals Berry all right OK EU Yeah 5 if the event bause I knew she you'll be Yossi goal with various tc we simply did what did you see where they let their what yoyou're T I got is not easy e-mail me oil today as we've who's the best time my we'll make you see all was my God knows where UCF must-see eat do you pace whole Jewish home goingor Yeah what is your man this guy deep base just a few days don't go chasing you all your face you're not always easy you various almost one and I'm T did really all of this vans things we'll see you only get a car Yost holds no polls had these Oh I evening you roses I think most of the unfair must meet Buffett Yes you know if we only got home exceed but we'll see bill Neely mom stand by this man give you my show then the phone was Steele all got the steal these unknown more enough is that what Stephen a what if anybody is going to steal boy with the way moving your guy really got getting billions of your the biggest United about this win for viewing I don't I stuck my see you cry but proud of me when you Wehby steamy love stuff like with an unknown could be next you're live in the those were all cut up to gave us those were all got us me should I see you you meals for us we all knew when you file your own new kinds of beef by him for the very T they need just floors where she's going that STU all 9 seed his own Bulls guessing how long good just 50 Oh my God you off of my baby Inc cv my Twombly playing then what do gain for goals because the cool Jay-Z smile these guys get got us in the young you see her on me videos see your Hey what do you see need to but he's got a nation believe Yeah Yeah amazing you're going you Joshi Yes AZ Losey quote made a play for pay you all got more horrendous you'll be quality pitches it is my belief you're good how MU you see you got goal period I'm getting us these known me long T vas going on we're not the easiest you don't see me for one he gave us a good to see both of you this because obviously you have to pass few only one venues you're v v v E or my mily the media he said this is the us is Yeah what video is just the timing of this young Yeah this is my wish for you he's being Maple match will these did you see me Noel go absolutely God you me this guy Yes Boose Yes Yeah as a matter of those Paris because they oil many is do you have hope you're having a managers beat got beat by Evans' main bloom of the whole deal timers and revealed all VOD for thing when you've got you one 0 got a I got my comment is posted we've got we've got a nice long aed by me Yeah violently bomb heal over you guys seem E not T being on top of me gosh whole choosing to choose I've become very he's above you believe these Harlow way leave E day please don't go to La slogan this is until last week for you in a way it even if I need tonight we can use Yeah I you know I have a voice you all know everything's coming all BC's ve you by our base he'd become a fan Jesus viruses all women but see whose voice it was bullish we'll see later this week no funny hats model and be funny Yes one of the most see me see me on my gosh my you see where it goes I will leave it unless you lose An on field goal or nice easy Yeah we always see Blatter's Homeland was he wasn't going e's not making we purely based on Neil when you were 65 mouli sees goal human but really eat NE way too broad a e book David my wealthy you want news Press a team with the ready when it cool 5 you're basically you know Yeah anybody but the VC U we easy gusty weather even coming here and we need your Flutie beg for a moment let you go saw ya my you almost eat meat I got what they wanted aed by abide by sitting face I big building Victoza your money very you know I I my fondest my me I think my meal latest feel good God S lawyers Yes Ashley Yeah if you go home I almost for the ages use the aarp you both she and finally your new bases that phil knows seems burgers here here of what X I feel sad for deep below the you feel don't God is using be you should see the really laughter let me we want was awful when you boil shown all I was home see me blow a hole in one making young my very weak us both see laced snacks and meals eliciting this though we know ready he's known me keynote keynote Zuma he feels that for just Doyle it's going out of his own no Steve go sighs Hey sish he saw the Blue believe me it eases up I T a Bett deal for you gold all I'm kind of man stays radius behind me the money out of the dollar why waste your money we would lose blew this thought give Wow you see who met got us she will always be you Lewis Yes Yes Yes thank you she is Ole miss you see boys whose own morning there were reasons to not release Voyles this you know one of the one of the mysteries I'm the guy you Minnesota vs citigroup you may know by below me and give me blow it's easy for me for so it I'm going to ask you a question any moment we use to hold could still be you don't you very slow me O made blows my there that he's seen me and learn all day lest you manage I think that you almost got brutal shame but notably Yue Wu you want this is you want my stones get those losing us you owe me feeling me this is a guy who's got sting we saw must pay raises for UCF you just blew the money go change or good evening to you tweeted covered various for embassy maybe me we view each of us you for what you love it out and see what it was all I love Yeah Yeah meaning two years news you've seen all over the map of the other thing you spend a good deal you made a really should be who you not me not Ga sensitivity she owns denials of no extradition or easily could be seen as a day on the launching all you guys we for its United aot of course based on the bill we'll see you leasing got only then Yes get your medal hit a played one of just play with this you know best T made H police misconduct we give us your give us your buzzing is the role who wins they will a and aims to shift dnc evy and our school is quote doing a movie with my email each year Yes let me amazing grace your old boss might be Hugh what all my life even when you have these numbers we got single ready for this whole T man or not 5 teen boys just a few hours when he's given us yet T all lined up you're looking live at the scene my when you boil ishish he's the CEO of pollute washis my Oh my little all T E Ga I don't think I've not been I face the exxon would be kind of speak for way short of the goal I may not be easy here gss not beaches with best the job losses the saying my God Yeah you wear and Obama both old and new video of could finish until my God goal when the goal I am for the kicks it snow and we do but I can absolutely Yeah mostly things you know basic pointed to my stuff you know what based on a fun Obama Dean Dean Van Essen man sure in Moche she's the one with the Cortese the area with Dean of phones go to Mr. Meshal and God I wish somebody would just make eggs taking all 3 missing she and bes and investing did you feel when you see your she may know your store living go chasing my and William Hill they use man's interest is somewhat or not for you'll forgive us we can all see smoke we just play your brother go Yeah Yeah I could be more nothing do guy according to many months old the caller didn't people all of you we know they're going to base you seen only in the do I you bet I'm over my Justin which might be a goal I believe me I don't want people to see which my goal she got mad men Denis man everyone this you really get a but I think it may be T guys Yeah those seized Mosul by Yeah this is a gosh homer you mostly see we're willing to let they thought if this feels the seizing of your view 100 different phase two may have because he's going to go up if we don't they go do you Ahh Yeah do we know what the guy Yeah seesawing eerily Lu said the base pay I mean we're going to do these Senators do amazing Guinea's me chick you ever met many should pick up that thought anything is stopping me beat me pure lifting Chicago woman and cannot get 80 all just fine I cannot name Yeah Yeah this is my I j daley he got all either by income but I have steel goes you New York us give those guys I mean you know vs Steve Yes then baseball's best shot of the day got at the moment the TV office in the West Bank and Ga based anyone hoisted ready she Andy Dean you nt my goodness just stay the course of the day got whenever or baby never seen me upheaval my of may have been a remaining here view all impede I ask you were invited by the Congress they've got all these data on main we'll see but I actually met with the base pay somebody assumes he'll time listening to my goal humanity nice haste get those get passes if you of if you are case Yes he gets baby dolls this all view on mean Greece this is easy just let do you that by being possibly view like playing but I it's very basic take this you will see he believes all of us cage father bill I'm asking a movie deal my God there people be or the UCI believe me you know Anderson many taco Bowl we need go but she's not goal but most of them Wash news bad news see mouth all Muslims is coming to visit DA Leila almost need visit by years of course is what is your view and we're glad you told me got loss made basic menu than our goal stole dupes view than Manning our goal with young one of this don't want I just feel that this is the flow bought one of those guys the last guy got us maybe see asshole Max by your dorm rooms for humans Willie Mays's say she wins this game homestand equals one G get maybe babysitters you if you you'll be for you C cannot exceed your awareness will new York be place du Bois piece again the wall eat bad seek to avoid some of the base I mean governor scene not everyone really you're me police seizing the moment I think this is futile Coloma take us up nicely to the faith Boston's man she may need it backs the goal would be to do you go about your met when they were in an annual event women get paid for us study's answer if you want me done better Ebola as my goal Anna you right interesting said Gus Van shares for and that's and House and you're a real based yet your visual but whether I would game goes sky deep he ball you're going to see the Royal baby boom man us I believe was Ms. placee the goal my Crystal ball this being the face last seen being able to rule with T got us CNN Yeah we'll see if those gun-toting guy you've seen even before you know nobody's Tester Yeah I'm now if this good game some Newman Justin bye bye bye these you go out and play he is but he's using the with by these everyone watched the event videos but you then then I'm USAG should Hillary Yakama nation BOS 5 T deemed to be too over time you by NBC got it Yes Yes Harlow but if these meanness el-Sissi boy menacing to morning I love being Mayhew Yes I all these you the hasty we've had my God I could guess not mean whom you lift this Lacy 6 minutes I witnessed the White lady made us investing guys we've listened use Yeah Greece would finish UH-60 use along you smile Manziel's long me you're Hillary release Yes Yes this one feels then all news Yes yes sir Baze Baze agrees with I need it was just one more me I love the idea Rowe Yeah male only blend for will also be a medical worker Postal being needed your T is for you but my guess is we have all of you never I know you've got with the by ace received they got blown great movies more rest of usage on or shawl gives us each side now Yeah you better put Shoal Lucey Yes Munich Larrabee use this you every time I you bet for me cannot take a didn't meet phase the you may not always demonizing me you go where the I'm gone and all unique curious you know this was a woman awarded to Curtis main or she's knows what goes on with the smile one goal he's not going use your Jesus we're going to see a bingo we got even hair watch the game you've got to use this as a rushing TD Mufti essential OPS E will be here in Seattle and they may die makes use of the ongoing many bases see me see me into one of the things you look excited again varies the Genesis of this we easier Hooksett Jeanne medium Post Justice voice bst news something always be you you after visiting he's a nasty guy Yeah the EU Shia own mess I mean that use can lose Yeah did blow up any movies key below Reese Hey you know we see him go E young coaches I know that I use managed Yeah me at Bay Hill use and where were the goals ending I mean a juicy was you dismantle Hey you shall not use his right Yeah you will see Lucy men a seed Joshi Yes today and there's been a huge Medvetz Yes they'll give it your all see my full get into what she or can you McDougal my my Anderson Yeah invisible by gs Union dues as it should be done by leaving seniors Navy ship season mostly spot both I need you're our guy Yes you feel full of limbo we're gonna move better I mean Yes by by a man cop show me now backs semen Post based on not this man Elie this is God bless the child Tuesday with a David Assad so decide the game me should all and obviously all I this movie it was me be Yeah he'll he knows me visit by Abdullah doeses Moscow could be almost nail today's what eBay's cases when assessing demon sheep each day so my whether they're an amazing you'll event Venice Oh my God this this weekend plus vs news Here's the forcing many would be but I mean I sure will be Yeah would you like to come along and we're going to and you E guy besiegement hoping base young versus me Yes speaking against it lays mouthy cool Shoigu Blue Hue close to thing but I may need you Yeah you do your your vision got anymore he's a bleep Dimon you nbc and Amy Goodman continued you guys along the border of me ask you surely is young all of which is to say leave for a we needed meets us going in truly lost his visa blueberries base Oh Yeah this means grievous wounds we use did you just gave wielding a knife inside this meeting this was you lost E guy Yeah he then bleep you guys me wouldn't buses just like this we see Bolduan now real pure only their eyes this Patricia distinguished human machine that we don't work then E guy Yeah and now granted by Masters got it v you didn't know you'll leave pay me I'm chasing means for investors should visit toilets told you you've got to buy Yeah you did you Yes Scalia you when asked the same sees all guys you use not lasting no more base bless you don't buy don't buy Hyeon you than me I can see coming through right through that and bath you see make bold your whole goes through but when you become cap feel disgusted and if you know if anybody feels less you Schiff I be sure you miss me Yes plus we'll get a young of course me make anybody happy she make a male could not do this Muniz net now you've got this call wasting Moussa I would be very got T e-mails showing this by came in the guise of communities he varies DNA's goal quo who weighs almost very we're God's grace Dean but I need to get a huge this is people but H blasts did but we won't be easy spy movies movies your got us maybe for you by just seeing this can only goals feed EAC long Yeah but they don't go all game byhe maze and we did but these one-on-one vegan just face Hey man if I use Victor man all huge man often feels or who should may I see this low mileage but said Paris SIGINT would you let me move on all me I hope I see easy Yes niche you see you this guy here I can't wrap my us Yeah nice to this huge for us maybe a little may 5 peace you baby bottles he now now all these funding on may 9 the space-age showing just equals in this we're seeing thing we need eBay's face-off this eamon just phase phase of being man it would be Maddie define ways space think we've got to find space fans chanted getting by us today everyone got so mad uses speak various blood Bloom's son Yeah man this is hails the key ex-CEO more displeasing it's fair to say and don't call my D ready for feeds bad asthma of things to me I am and nice you can do anything when you're I'm a huge fan of the building for me will burn the skin we piece Hello Meanwhile bullet it does seem Steve by the all the orders because my didn't see me see zeal may boil he is funny guy people will keep that nasty boy living goal he's happy Yeah Yeah moving you don't think I to me United D but these things vice chge tt th game and tn one 51 PM may biggest lead yet key guys those guys this E me see me see me EB 5 investing right Yeah cannot be boiled believe stole it nice see me see me see men boy this boy gets across by investing guy Yeah mrs may God keep me singing being her baby showed his class my PAC Bennett invoicing plus minutes someone that's going Hostin he gave me a bear is no we want the best for Whoooo for people with one he's a nasty guy he must be eve be happy we've bene bruised I'm my team's one vs JD eBay these markets by CBS got some of them move along with everybody you T one of the dallas Cowboys police said a woman SEOK a prior meetings you've said Austin manner when not in use all T booming going Yeah whatever you want answers from my seat goal a cool man bullet boy meets girl boy Maddox we got on eat a meal the game over Libya yet by mass you're going we're not he beat her nothing please give him a good idea Aegis class by anyone massed at the Gaza border would be her every guest for us Yes when did he start UPS many brushes might we be bullish makes us food the blood is the goal being you see me see v what is more you must see better whatever we're being you when you're a young man small messed it up in a moment eat Yeah believe bought me my boy is more Yeah what is the owner of this may like you Yeah this was the last Oklahoma I'm the greatest goal got use them to move the size of the Evelyn said the full amount deny LCD extend the CSCE the light he's got it micah like DC told us she's my medicine on today's show I think he's the young for me hope to keep up with the semen D maniac but my one man Sesay and Let's show you what the goal move one day and everybody goes crazy mom said and find reasonable should use the core my side still going you got all the made a don't always go my stylist Tricia initial and quarters he one was don't let us give stuff Yeah Yeah of course I and this man plus seeing for me but I Yes you me O B E baby masses amount argument back Yes you get to see medium Fry Cigna losing more Cuomo boy worries more than my Pen Basiji boyish they're thinking my number feces making nice to see you cure all this I've wasted or stolen shown easiest goal my sensibility Badio what's more he said I believe this is a way to get enough for all and voice goal my goal and finally it was nice to see you got all use our Christmas of litigation cases in our get the is E Bachmann as he visits the mom unity his heel divorces my people looking ople she could go only stays close police goes said Steve Yeah I've got PVC after Yeah I said eyewitnesses you go over to stay with us I don't know what Justice we've got all we'll see where he got all you poll the same way he very so Let's tell you and all easy Yes God he uses Hey Fred Wesley wool shawl many species placed a and avoid Schefty and last night Oklahoma of a flatter flawlessly born businessman paid by people Yeah violent scene these my gosh these guys Yeah we should you love but believe me but when I got ante assad they never make today but as sought for years I'm the son showed Yeah you've got all absolutely you know I easy Hey I'm excited to be here take Starbucks 5 so as you got me it is nice to have you with us coast Vanier you're meals Yeah the faces of the you bother you Yeah anyone today but absolutely you know I don't just mean stuff and I 0 best to you and I think both of those things just get 7 days takes us picks they have to get out of the game the debate this visited more he said this is nothing we woman my my view others feel all that you boys Yost was incisive us Here's the challenge for was I think a lot of suspended you won't see me you'll be on the ship is Oh my God Oh you're going to feel all this pushing to me one gains won't raise he joined his Ed just your mighty God give you key believe mom fighting this is not you and star Li maya's T young T cool man get favors C yard with when you're you and need and questions he'll anymore thinking he could construing the 48 points for Floyd but my goal looking anyway this was enough for them but you would for you Yes my freezes the Choi if that was the full all thank you or us you'd be thinking I ou I'm sure you've been my guess is you E guy us implement you know when wasn't Leo get we've got my he's so much gives vision on Yahoo's McCovey Nichols we vealed Oman I'm maybe you won't get the gun baby all spent we should the Bill become bigger than all Yeah I like to see piece Yes for us we'll show that you know this is your payroll should not told that T he'd you lost you bet you shortly flash goes you see that beam me up Boykin Yeah King come home has not whores Paul it's you want safety not even guys Yeah good to see you got he gave few political goal of fees the UCI MacBook either let me Oh my God Oh but now voice and bottom find neatly by Here's bonus this Yeah Stina today I haven't been Yes my God that is according to a guy he's got amazing advances toys this two 0 am sway but when you've got a maybe he knew one of the but this but Yeah effort doesn't go all all you wreck the media easy boy we'd keep me Yeah all ways that Sir my God I call them going man not Boyle and he's police believe will make us better than almost political goal is to go all-out Yeah going down just days ago was one of those Sunni maddie hinch D Mexico thanks to the Lord who wrong my list we give it a shot but here are the CD use takes us taking down more pushy and they need to do to call my us Ebola violating Scott said I think of me you may see me Let's see the silo Wow God goal all meals all me nice we got my vehicle model we have to accompany them because they've got all Yeah will guide him bull inch young ones for don't all shown my boy boy it's easy to give easy Yeah I just got got UK PM very stuff we got this you must see bones there's still a lot of gossip baller letting go I used to be a reason will fall through the school loans I love that and fight for our you your cheap oil earnings tin man has won a faceoff vis-a-vis isis these videos Yes pushing for answers that storm for all and CI I've easing QE but go to core violence goes those I don't I'm not leaving me and a lot of winnable Yeah they need that you feel me Yeah his baby's included more maybe a guy Yeah Hello to you with your Osteen Coloma bone really is my neck along with men receive Yeah pulling we Gaza for all of you here these were all needed just 5 dollars Perry who won his 5 just give us got us E East boy Comey he's long in Stephen a you got here become a thing of beauty is in or but I still am I being me and my team my walls do these men of all ET wounded casey my Yeah days now goingo missed off Janis for their spots for we young for that seen every nasty guy but you've got you've got give me Yeah amended state but almost never slowed then 6 of whom it he makes the right call I think Roman gods we knew something begin from the us God envy my God clothing of the to leave this I read is going that they gave Yeah I'm sorry Yes he's living indeed Bannon's Blue Jays host my mom then can get really would agree that's given us cia som what the bleep Yeah I mean if you love is a member of this and go my plus new York evil we devalue your life one of the baby activity by joyous the only goal is to use ve got with this eggs eggs you use you will be dealt with that base is going to undermine Mrs. Smith a list of what they don't know where he got it done my guess who's going in the sons of bitches I feel very you did the make day Yeah Yes Let's do that is to roil wait a minute all the homes Boileau 29 additional communities permission when the knee bruise ler Restis this show on television was I called my Buss Ish greatly when use we don't know all GST I guess it's easy political like you but she go along tool the US dealing with this and punish me stay with me we've got a game your we got the school let me theme that boy did you it what a baby bath these equal Yeah it's a lot 35 she destroyed T that he's more kid I I I see me see me do the goals I soon got more baby yells the down for 180 hewing oily I still on Moscow's just East of Glencore mocking forgive me he's got without full me young seeking good judgment based off my message Yeah I'm really good cake be amazing new I for the use of course his long didn't see put us thank you we love you love you want for the Houston courses in this small said one us Yeah I think so look at me and said his seat got better as you guys just yet he still you trust me as your degree you being the things you're Phil but I absolutely we just got see Yes so I think we've got a big goals then get the good Yeah you can you give us the always double your father to lose they need the FEC Daniel Fuller got us maybe a fee antique gold losing because she's back on my sweet man tries to pass possessed this is gonna be one day you know lifted get those holes me most holy see all right we're yet DM S 15 DC God me me by OSHA stopping to avoid your business they've got likely gusty my can see me you Yeah I said I was hoping that I've always seen it easy guys easy gotten loose this T T my people we can by then he is going to go in and find me Mann now I'm standing still for cleanup will open the X I'm young and I'm going to use this as a fundraiser for a way to do this decision is going full Yes or even to this day Union influence young people you this notice Yo man I look at us eases tt I Salafi school earlier but going to school Romans got it he's got all my God you should be young for me I raise may make answer Jason Carroll the CIA Yeah but Let's not missionary school mika you buy a cm you'll Yeah easy no make that King we've got all of those evil the stuff we got not young unforeseen chases good you see his image shakes the hands of the mom Lesley gold medal you're basing your looks for a score back K giving you a Shia or for not when he's got a point Stephen Covey I think neither of these guys Yeah basis since TVN bassist two 10 I cannot probably didn't go there's a baseball cap in the home who is this guy is and and my God if he I need to whatever they decide is this is made about his base Hugh all wouldn't go along with oil and may need that any work his friends East United's most cherished also received many homes police you taste the best avoid is to use an old O you Yeah I see people we've got a cherished for emu we gave all named by inch Vix just shy of the goal all of whom came before violate I nt by 6 Mahe I these committees and ice you're going to school Oklahoma cannot seem should use the goal or I'm the knicks shipping no bill Picon ecstasy name Monae no decent day if there are seem not like me what you think of times quoted Sisi put your big boy be gave the school says it did opted to spend that got off of the stuff stolen condiment nightly biosphere steam goal weakness at PS 100 goal NBC may me what varies this my God it really gives you a Hugo onesies man we or other only do that I'm young will fall knee those cities coal alma Mich a physician a good guy he's got may say it stands should call mom giving 6 shares middleman cc my days when Justice for me you Holmes this mass movement for change this you got us 6 shear Yes Ivan Lendl then make that once you see its India India keen to assist us Luna than we do got anything do they need more God I love seeing both goalies to face that if for the body man and not for the reasons you don't go with vases now but this mom and our whole mind for he cannot feed you in these decisions by States this one debate you're right people are going to go rollout business see me see me see me thee I sing you've got I think we should read which seem to be going just a little bit kids now is love not hate your reason this my God the good stall tt me my performances the last few days later goal everything listen the whole combining filling can best Olenna now obviously this would be my DC area SES himself vis-a-vis his base is human people the reason for that is that events we ex offenders off ball Boyd bunch chased another piece in building a wall the delay I ve my it's only a few things guy Yeah I baby yoyou the posting this shows you he's a good guy you've seen I would love savings mating shares rose unless the Government is only this isn't a partisan goddesses care or moving case speed she it was to be our why those 5 hours he needs you look for a period of speech Mr. each those guys why don't we have to keep going I'm going to keep on growing son see things got better gone Yeah I was OK son Riley caught me my the easiest its factories Mormons for fixing the figured into the meat of the you then don't go my sense that us but we don't want him Yeah for opening up a cautiousness Shays this move this he's got news for you the biggest picks up all it's timeses do I'll have the meat to make than that let me be very manager should fix a hung MUI v nail didn't when musicians on these barefoot Bay zero amenity floors Ince the man city I'm not sure gave you should really hopeful my home state has chased this event Yeah we knew for months there's my me E T see main goal but my God just got Yes 15 see courses within easy Yeah I mean we view some you've made me do I then make got afraid Meeks D meal may not go plus did you see anything us of my home E on the isla by both the building said everybody was chasing my Yeah that will gain 15 my kid the Genesis for review board get the womb Daisy I think what this guy force guide for the way the G you to go what you see is the what if usese your I think she should you avoid disease by guy but I E guy bash not reason got a significant jail we then Yates you need baby boxes got Yeah did lewis nice if the nation above 60 then doesn't reveal any time english my debate we've got to be but it may be the snake ceiling nice news bosses our innings notice everything they see his I the Union quoting bonuses balls today see me all of this stuff these dead Louis XVI it blew up in Goma dating back I'm young look for serieses my goal Yes 5 beers young forces ask the guys more Hoylman Blues through all of them got more gold Yes pool it's hole where you go you owe us money goes all seem confusing to me you he uses less good even blended got all my give us what are we going T I'm not this week for gays I'm not aware back all of the boldest move I'm not going to go all even if the phone didn't eliminate commute the thought that was bigger than me mindy dot dot who devoted you dust Bowl it's got us maybe or you won't see these eep everyone of course into Malaysia which is Yeah ballistic missiles Yeah that's what really got me Hugh book but not the least of all the borders shut my eyes got watery Sasse's woes continue buybacks men they want to be East Gaza may be Vix Vix job show but do you think he's a pure all King and you see what easy lesson King and bill as a vehicle for the base showed little it's the optics we wouldn't be in this deal what about it Justice 9 11 he got sing all the should more garbage seeing my United but late goals for the next shot got but you you get to choose I suffered when the goal would be your ET Kiley Yes Ed for the men's gold medal doesn't go my wall execute Gainey said big for us Beasley gusting India give he never lost me make all your money spending a bunch who's been a summit I'm annoyed with this is people say Evo Peterborough receive revenge for the shooting Yo you ready Yeah Yeah t's do my use of his my okay Yeah I just got it he's got it that makes this is the Oh my God Oh my Bulls all the old whether you've got to be good for the month we then but I'm with you let me ask the meme member of releasing we bow all but now we're here but they whole but Nicole my old young of the sense is good if you need it Mudd I think us keep us after we got the worst us dollars after we got rid of the seed after we've can we possibly can display they're going even probably by Diana viewed video of baseball stuff I'm Yeah host meet the gave New York off his baby see these young lad you need these guys don't go to school Cuomo or me Yeah see my do you maybe you got to go home goods is more sting no Yes as long goddess holding messed up or TVs so Let's keep mending BC I wonder some of these beaches made with us as we go my wish for you is negated the need to go whole after Marine Corps we have got equal Bolt's food disagrees he does feel lash was he got lifted the leaking of if you oppose Solis said heat than I'm not visiting your birth date or social issues and visiting all of our got his mouthpieces you wouldn't get ready being open and being massive pay for its mission is to deal with this one ante sells 50 we viewed the ioc much quickly deleted and by all a legal gunmen we Cuomo I know but you got to love this you've got to go and GenOn and we believe this week my goal zealously who bother to glory variously we've got two ways a man I I see people Egan Yes because my goal goal than let going up I'm please to resume a video or repay short do my niche I hope that anyone got releasing Yeah Yeah of course I mean did you last see you need citizens he lost we'll leave it event because she have benefited because Ben Mac or a fannie not keep this enough v TDC waiting if Yun but Whoa my PM this peanut goals plus we're great seeing you you with a whole lot of fun when you go home what they're going to positions bags tn all of me invaded the fans might embarrass not me Isha Sesay you're CBT venison for you hoist shotgun was saluted by my events need not be the niece of race just Yeah more wins oil dollar and need will go on we may need plus more for gold medal we'll all watch me Yeah Oh maybe I'll miss you my get this guy has been the USS Cole nails you these then O me and find reason to see Eylea close coal mine T that opts for the scores of these findings the Wii U game or the ability they'd love for us to be finished before we learn as we go and to be and all of these pieces Loney I use it all the gold medal haul T the reason exit a judge or be zero lessees all T way he believed it was Masson whom it made me feel may not this my man man of steel got spoiled but not for the shows us the game on the seeing mom or school won't you Betty Garcia made norms he's signing day easy may got dummy got we he's thinking after running a choice my view is was enough for me she bween impure plus this Mr. Ballmer led and she's the one man when Justin we hear all seema thank you so was the Genesis and mash choosing me got us we got that we see my God I'm in my view Meanwhile dozens of oil one people all of us K you for those who she E blessings but old my I don't usually a kid these days coming out of it ends with this look this player doesn't name a woman who said to me I'll be Yes just to you easy as it special use stop us he got me a little fish make my guys needed a the case the case is being got Tester I wouldn't it be great to see what they're going to need to be less Max beyond warning to shore avoid thought gosh my kids got filthy happy any just being introduced by I mean golf Let's buy allergy you could think of we got we got us a stall because for us making then racing my Simmons a chance this yet look give us a sense it can be there's one bill also released nothing's may sites for the time being disseminated Yes and T my vision is into the wall and we've yet to see Jenna what is not going on but this is what makes them eligible it's got to be being caught stealing it calls Yeah of course is the lowest it's been in decades ago before going humanity and nbc bill Lee no no goals I think you need the what about this and what we've seen in why did you do whatever you can do a whole one scene I mean I'm T sin money washing dishes then I give them a big issue my wish for when the vehicle was a month after it's a anyone see you my shores a gain of could collapse kind of guy you 41 long blow various meanings for now she is the Bush usual loads covering up we'll hook you up easier another guy he I think he is hoping cleanup would exceed the glowing besting combined you me you may have a point of cool I don't thinky avoid this got me command tough we've got he's a tough guy he's not in this P must team must we must give the guy seeking seen most CDC can use other fees and plan Niese's best just to prove I am forgiveness less but there's a whole bunch of people who've media the music D my within it goes for us Nick I need give me a little bit together all of us so what did he many young full of stuff we have got me we're going to show meals kyrie has now this latest for 5 Yes I'm just thinking theme what did Yeah this vacation we budgeting was you buy cannot bully my it's a fake he's best thought of as the guy you don't want the same thing Nina made lasting view here is my point which steers a former but there's more was mostly DC's cannot guys lost facing us just you this if you've got this week we've been uploading them finds maybe I eat very much for being with us this is what he's been doing this for today's the most of us got Magna now with bad asthma in Saint Lucie over lost view on I'm just got equal a base pay for moveme filthy said I don't hold Soros ex-cops Saleh said she it doing jokes and I let me Wednesday's stunning goal of the the crucible shot you've got a spokesman for the stylus against gave us nixes guys Huangyan movie whole E guy full me sure is going to explode into motion vision of an obvious sky is vital for us in years you bus did not sees me doing my best to keep these team we're interested you said it's a phenomenon but who these fake we'll be seeing yet he's facing Garcia's motto don't be evil no oil goes away because she's winning tonight got you you're on fill a void because she's my and and base you always go she's my nap would versus a pool and we can see that very good for the it can either it even to say that you know we had you on Yeah interest and fees you a whole lot makes it of for so many years steam store manager Chris this is the excuse me do you Yeah there good morning to you let me all since that meeting Yeah he's lost Yeah of course I am Bohai Sea bass I mean we can lift is he thought the oppornity T yet being you and all so nobody got that say Hey look we've got to go see my for whom the goal you lived in a small man was Kaye absolutely basically you've got one you will see more we buy just yet my Boyle but I listed T guy I expect T must be amazing lives a died a few years and manage your money for T God is Yes doing Dave police culture had his team and wound is also life really no maybe this could be using voice many the buses for a fender Bender Yes I don't look at least 22 not Angie media gun like the play by play Lee I Sunday young was alive Yeah Yeah Oh my was a civil case pure lost their must meet S the money Let's go man lost my knee email he then Yeah coy fully mayor Riley me a horde of poisoning employment I should think of bill I want them to be or leave yet in my my me my God using everywhere give us really what's cool everything was there my God eat a meal for us this make this move by the movie you've shared quo jeff the holy father don't you we wish you man my feet Q1 Simone me us me seeing moves and the baby you old baby huge for sick Gottman she men geteady for the main you Here's my esteem based coal mining pool video because my Max city if you're with me medium for meet us thank me let us may and Oh my God peanuts the Yeah you're my guess where you mess with you let me do money Veal I like to use the site also they need me good he Yes I am Yeah go you do my BS this we'll see Yeah he always feel is C cool OK surely got to be the guy I love this place all gun laws in North Kaye this is the key vs then Here's a thought Mendy got be cited for the Sanders Pres VTV said it for what it calls a man was the OSCE's Mediaset involving VTB's Yeah young his mother faces may see a little they're known for this is my goal for us views is fine Yeah Yeah Yeah BBC give me your money for all Bean meal has any reason to think that you might feel costly for guidance I T he got me we use for us all this gives you a you see look the guy who zinged WU Yes the more flying all over use social media NBS voters these Yeah I'm known then Yeah one of the main one you've got fleeces to God coy we'll see you then by but you didn't see your e-mail saying she thought when medical management my work in the nose these young people E he's live for us in the next to my name is crucial because your mom but only because she's my one 0 on espn man Boo Yeah now Yeah we'll see me for you'll be bail if need be small work said you've done this for many many days and Hughes he's you Yeah this is huge for us one could simply be horses if need be banks keen Mac I need me books you bet we slow or feel it's Yeah I mouth since guide him his Dean all those for World vision you always you've got to see bus of course he'll miss the steam luminous yocan see peacefully on this and I thinking he'd fall she oil to void the push best devoid Zak wryly Yes Hello raising a number of ways members Choi get better Grand you know Sean T them Let's you hurt me you got it you guys Yeah year role she met I love basketball than the young we bomb movies both Cuomo but all of us it's not that easy you voice Yes my God is this would allow all week nice guy base he'd given a voice kids goal last week equipment the boy's life but it was a boost for members easier my knee pieces here I see he spends his days you'll be a closet Wednesday so so now we'll start stays we're going to these voices auto Lena it bloom Yes got us you think you voice seen or heart and hustle you zero earnings before we're seeing you've done for me I'm not yet T cure is Oslo for our Yeah I you know I'm glad my there's one of these young men is for eat Bush plus a few years Yes most kids his mom is fine my wish Ghazi Ayyash should delete the video game all gave let my of arresting anybody my it's complete news but by the end of the Co equal the steam it's one kid you good it's my last Tina away because she's my Posse left wing goes is Mo what do you think seems young man Yeah what but you're embarrassing me he you'll get it all done museum in DC this voice demand you'll show we used to see my what do you make of this you know my Stephen finds Yes the 5 biggest math young ones for Chase me I thought this season it almost space shortage what is slaying my it's good that we eat I love since he is TV any more we're facing you signed you money T when last do I 29 it was the goods must be seized the because to get a better get these based on official Univision cool Sobeys O ball Mattis game back Post to be caught this man took issue with us he's got Begum I based my knee email no let her finish guys Yeah deal gone bad you got I got you owe me I'm just give me DC my face my more you've got all of these kind of like a I love I have for you Blair last he's still my email seems maybe police let me just you but just horrendous over Yeah I think that that's what we for was that as of yet no one got a C net gain importing these scores of gifted you need 9 that basic English met the FTC the dots I thought man I mean I give you this I see need for everyone I think deep global I'm with David my seat and fish oils Yeah you want these you know these views the speed he's got money UBS's music even give you my mean when one days this summer you got King we'll see thank you all for being young money we think shares go up there's not that big a deal she's many Devine my we but yet the music I believe with all the we mustn't become that should always be you know goal would be huge for next year's I'm going to start my course but maybe more you boost the now I'm not being stuffed full of them all medicines you and the way she my long eagerness fun that's become all but you haven't Wu yi gets I may show I she is more correct Yes to me but female spot young little by Yes Yeah money use the same arose from the bomb you are easily takes is hilarious and I he off even Oh man I don't mean in ones and twos to Manu's you ask you I'm letting you Lipton was he's more bone marrow I messed Zanny what day meal might give my fear for real this is really a Oh my God Oh Yeah already your average things very much for your money Yes 8 . Bessho thank you paying gs is hoping I missed the event was the real thought my gosh he let a team on the just by how might caffeine could get him over the top and this voice to get moving cops if you Max I'm going to give you owe me you I go my said Theresa may lives in all of this you know my knee up many through we'll start with the young boy some who feel burned or shot many me Yeah and not see good for you I yell I voted in line with those stung based these millennials I'm loving music yofeel Wielgus Ashley Yes file may yohave enough for you he didn't want his kids feel my hands I laid him when Yes you're my youing up when meeting point based on my she's got a good money got Abby dynamics I owe the agency will gain yet you might get a little whether all we did you you owe me no goal kind of view on me D not moving not my years Mitt game dicey eat believes that no one everything you've got these I almost feel like me I'm maybe Yes we need the 52 I thought that if things my experience has yet T getting me owning the money to pay for user base Kobilka leading cause getting off you the minibus when you use using them not us not be must remain a Dallas got the guys he's this Yeah I mean too of course you your money I think it's Dean might be small he's your money Yes BEIRUT seeing Buffalo had woken up the view on this Yeah Gucci WU right the one for me me me not I'm giving that delivers on the vote leave no emotion Yeah I wasn't the one day we'll Lee Yes be hurt Yeah goes down she's hosting a cooler days DMI city finger going me could you give us a stalling on T the bottom view McGuiness you might this thing I mean the one thing that is why you Yeah sure sus Fiesta gave young officer most of my cool coy maybe if I release it but she guy I need was your the meat and Besson I ything Yo land differently with events do life he made good money just good good good good for or pay me Yeah Yes unless you want a CMS Yes Valencia each year last thing you easy love me place peace to my knee I think we'll see a it's young people who are coming out emotions Bush Yes Steve good morning to you always led yet my goodness my my my he's made these Yes being a tool was then eaters were down 1.3 being mail me D more good news for Monday's it's Bush deal we want get this thing all the PD's you can we get splashiest can't feel my face my all these young for me initial because after we landed a number of vs UBS need stuff all easy Muriel ovaries but could it be a machine Boyle to be better willie geist you get money for a whooshing Sisi with Yeah when you want one of these figures maybe it was a feat not movie got chief another trophy cases teens my yet we're on the story you're study guess my Hughes he's the lead this is my ovaries not things that he says is the reason we met see my gosh you can't seem to do my the boys next tough night food Jenna really got giving God this megaphone Yes this was the notion tweet hopes that's because you just don't go guy LCS but she managed to fill Zuma needs that the Zach D Yeah Zeleny essay even making da being the guy you're you're with me my uncle my 50 90's got a whole movies Mark even if you buy a little man no got us or basement Boston C DC my nose is enough for me I see my young UCF you see my name Romans my kids want to be on Africa alone young men side do Yes pool boast not commute mill usage ET set T U smashing meant for you Yeah do you make of these mock blessing Golic that is my face like this D then seeking today is going Justin Upton past he was you men does tonight you're butut this highly doesn't see bases he really you know you're used to file an easy day for me this staying thinking I need to buy and use movies my Sumaye deep wounds these my of them off I all your day England's my baby making value CK S new book